Study on post-accident aerosol retention behavior in microchannels of steel containment in passive nuclear power plants - Yaru Fu; Zeyu Chen; Qiliang Mei; Dawei Sun; Shengqin Gao; Meng Li (International Journal of Advanced Nuclear Reactor Design and Technology)
During an accident at a nuclear power plant, even if the containment is not severely damaged or fails, radioactive aerosols can still leak into the environment through microchannels that potentially exist in the containment. Unlike ordinary gases, radioactive aerosols deposit and get retained in these microchannels through various mechanisms, thereby reducing their leak into the environment. Passive nuclear power plants rely on passive removal mechanisms to eliminate radioactive aerosols, which are highly reliable and effective. The retention of aerosols in microchannels of the containment is also one of the essential passive removal mechanisms. In this work, an analysis model for aerosol retention behavior in microchannels of passive nuclear power plant containment establishes, an analysis software is independently developed, and computational analysis is conducted. The analysis results indicate that when the flow is laminar, the primary removal mechanism of aerosols is inertial impaction at the entrance. When the fluid is turbulent, the removal effect of aerosols is superior to that in laminar flow. In passive nuclear power plants, due to the external spray, most areas are covered by a water film and therefore constituted as wet regions during post-accident stage. When microchannels are in these wet regions, compared to dry regions, aerosol removal effectiveness is enhanced because of the extra removal mechanisms thermophoresis and coagulation.